Efektifi tas Huknah Tinggi dalam Menurunkan Kadar Ureum Darah pada Pasien dengan Gagal Ginjal Kronik di RSUD. Prof. Dr. Margono Soekarjo Purwokerto - Made Suandika (IJNP (Indonesian Journal of Nursing Practices), 2014)
Background: Chronic renal failure is a disorder function of renal with increase of ureum level in the blood. the therapy of this disease today is by used dialisa ( hemodialisys and peritoneal dialisys) which needed expensive cost. Thus, its very necessary to found new method for decrease the ureum level. As specialy lavement therapy.Objectives: This study aimed to know about the effect of High enema to decrease the blood ureum level of chronic renal failure patients.Method: This study used quasi experiment with pre test and post test with control group design. The cronic renal failure patient took with purposive sampling teknics consist of15 person for control and 15 person for treated group. T-test was applied to analyze the data.Result: The average of blood ureum level before and after treated by 3 days High Enema are 257,40 and 355,98 respectively. Thus the average of blood ureum level before and after in control group are 353,86 and 398,97 respectively. Base on the t-test the diff erence of blood ureum level before and after treated by 3 days High Enema, found that t value was 0.309 (p = 0.003). Thus the diff erence of blood ureum level before and after 3 days in control group, found that t value was -2.157 (p = 0.025). That’s mean the High Enema has an eff ect to decrease the blood ureum level of chronic renal failure patients signifi canthy.Conclusion: The High Enema has an eff ect to decrease the blood ureum level of chronic renal failure patients.Keyword: High Enema, bood ureum level, chronic renal failure